2014
DOI: 10.1093/cid/ciu537
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Doctor of Pharmacy Students Regarding the Appropriate Use of Antimicrobials

Abstract: Pharmacists are key partners in antimicrobial stewardship efforts, yet their degree of education on and attitudes toward this topic during training are not well documented. An electronic survey measuring knowledge and attitudes regarding antimicrobial use and resistance was administered to graduating pharmacy students at 12 US schools of pharmacy. Of 1445 pharmacy students, 579 (40%) completed the survey. The vast majority (94%) believed that strong knowledge of antimicrobials was important for their pharmacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 9 publications
12
85
2
Order By: Relevance
“…Answers to questions that used a 5-point Likert scale were merged into two dichotonomous categories (strongly agree/agree and strongly disagree/disagree/neutral, often/occasionally/sometimes and rarely/never, very good/good and poor/very poor/neutral) (Abbo et al, 2013;Justo et al, 2014;Yang et al 2016). Data were entered into Microsoft Excel sheet version 15.0 and exported to SPSS version 15.0 for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Answers to questions that used a 5-point Likert scale were merged into two dichotonomous categories (strongly agree/agree and strongly disagree/disagree/neutral, often/occasionally/sometimes and rarely/never, very good/good and poor/very poor/neutral) (Abbo et al, 2013;Justo et al, 2014;Yang et al 2016). Data were entered into Microsoft Excel sheet version 15.0 and exported to SPSS version 15.0 for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The surveys were administered to final-year VM students during whole class lectures at the participating veterinary schools. The students were instructed to abstain from using resources or consulting peers in filling the survey (Thriemer et al, 2013;Justo et al, 2014;Wasserman et al, 2017). They were also asked to fill the questionnaires on-site within 4 hours to ensure that consultation of resources and peers are precluded (Thriemer et al, 2013).…”
Section: Data Collectionmentioning
confidence: 99%
“…15 These future pharmacists planned on practicing in varied patient care settings, with 53% of respondents planning on entering practice immediately after graduation. Among respondents, the vast majority (94%) believed strong knowledge of antimicrobials was important for their pharmacy careers and more than 80% desired more education on antimicrobial resistance and appropriate use of antimicrobials.…”
Section: Current State Of Antimicrobial Stewardship Education In Pharmentioning
confidence: 99%
“…In a survey of 579 final-year doctor of pharmacy students representing 12 US schools of pharmacy, Justo et al attempted to characterize pharmacy student knowledge and perceptions of antimicrobial use. 10 Respondents perceived AS as an important health care issue and desired to learn more about the topic, but achieved low knowledge scores. Such data support the need for greater AS education in pharmacy curricula, and the authors suggested opportunities to improve professional pharmacy curricula related to antimicrobial use.…”
Section: Introductionmentioning
confidence: 99%
“…Documents provided by the Accreditation Council for Pharmacy Education, Center for Advancement of Pharmacy Education, and American College of Clinical Pharmacy provide recommendations on general ID-related educational outcomes, but do not specifically include the term "antimicrobial stewardship." [8][9][10] The principles of AS extend beyond general ID and include particular attention to system-based variables that may affect an intended intervention's outcome (eg, information technology capabilities, interprofessional relationships or supply chain management practices). Although AS is not synonymous with general ID, AS has emerged as an essential component of ID patient care.…”
Section: Introductionmentioning
confidence: 99%